Polish-Belarusian Relations: Between a Common Past and the Future - Wierzbicki, Andrzej (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
This book examines Polish-Belarusian relations, which, according to the Polish historian Marcel Kosman, were 'very close, though not always idyllic' (Kosman, 1979, p. 6), or, as the Belarusian author Piotra Rudkoŭski puts it, 'Historically and culturally, Belarus and Poland are Siamese twins' (Rudkoŭski, 2007, p. 185). According to the author of this book, the nature of Polish-Belarusian relations is determined by their historical and cultural positions, identities and geopolitical situations. He underlines that Polish-Belarusian relations are subordinate to Polish-Russian relations and, to a significant extent, play a role in Belarusian-Russian relations. The author pays attention to historical and cultural determinants, Polish policy towards the East, political, economic and cultural relations, and 'difficult issues' such as historical dialogue, national minorities (Poles in Belarus and Belarusians in Poland) and border and visa traffic. He tries to understand the circumstances and international interests of both states, which undoubtedly adds to the book's value.